Advances in Hydrogels - Liu, Yang; Chan, Kiat Hwa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Hydrogels are a class of soft materials with crosslinked network structures. They show good biocompatibility, biodegradability, hydrophilicity, and mechanical properties similar to those of tissue, so they have a wide range of applications. In recent years, a variety of multifunctional hydrogels with excellent performance have been developed, greatly expanding the depth and breadth of their applications. This book is the reprint of the Special Issue "Advances in Hydrogels", which focused on the recent advances regarding hydrogels, aiming to provide reference for researchers in related fields. This book included one editorial, thirteen original research articles, and three valuable reviews from thirteen different countries including Canada, China, Thailand, Mexico, India, Saudi Arabia, Chile, Germany, the Czech Republic, Colombia, Romania, Israel, and the USA.